Metode Pengembangan Ilmu Perspektif Barat dan Islam: Implikasinya terhadap Pendidikan Islam Modern - Masnor Maltufah; Imron Rossidy (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Modern Islamic education is currently at a crossroads between two major scientific traditions, namely Western epistemology and Islamic epistemology. This condition has given rise to epistemological tension, namely a lack of synchronization between Western epistemology, which tends to be secular, and Islamic epistemology, which is holistic in nature.. Therefore, efforts are needed to integrate scientific development methods from Western and Islamic perspectives and their implications for modern Islamic education. This study aims to identify the characteristics of scientific development methods from Western and Islamic perspectives and analyze their implications for modern Islamic education. This study uses library research methods and focuses on analyzing theories and concepts of science integration from Western and Islamic perspectives and their implications for modern Islamic education. The results of the study indicate that the method of scientific development in the Western perspective has dominant rational-empirical characteristics, using approaches such as observation, experience, experimentation, and observation. Meanwhile, the characteristics of science development in the Islamic perspective do not limit knowledge to only rational and empirical aspects but also open up space for spiritual dimensions. Islamic epistemology places revelation as the highest source of knowledge, which is then reinforced by reason and empirical experience. The integration of naqli and aqli makes Islamic epistemology holistic. The integration of these two approaches encourages the formation of an integrative and holistic modern Islamic curriculum and educational method.